The set of indices of convergence for a Boolean matrix class - Bo, Zhou (Utilitas Mathematica, 2002)
The index of convergence of a Boolean matrix is a much-studied quantity. This paper presents an explicit formula for the set of indices of convergence of Boolean matrices with at least one pair of symmetric nonzero entries.